Azerbaijan, the door to orient between transition, globalisation and European integration - Figus, A. (Культура народов Причерноморья, 2001)
Now is near Baku and not so far to Italy the Azerbaijan. After three years, with exchanges between the University Sophia Antipolis of Nice, the University Pierre Mendes of Grenoble, the University of Genoa and the University Rassoulzadé of Baku, the Tempus Tacis project is closed.